APPLICATION OF DIFFERENTIAL REINFORCEMENT TECHNIQUE TO REDUCE LATE ARRIVAL BEHAVIOR OF STUDENTS IN CLASS IX SMP 61 SURABAYA - Azizah, Erliyana Freida Nur; Sofiana, Sofiana; Syakh, Erik Farhan; Ali, Sri Liana (Jurnal Kajian Pendidikan dan Psikologi, 2025)
This study aims to examine the effectiveness of the Differential Reinforcement of Low Rates (DRL) technique in reducing tardiness behavior among ninth-grade students at SMP Negeri 61 Surabaya. Student tardiness is considered not only a matter of discipline violation but also a factor that disrupts classroom effectiveness; thus, a classroom management strategy grounded in Skinner’s behaviorism is required. The research employed a quantitative approach with a Single Subject Research (SSR) A-B-A design. Five students with consistently high levels of tardiness were purposively selected as research subjects. Data were collected through attendance records across three phases: baseline one (A1), intervention (B), and baseline two (A2). The intervention involved providing positive reinforcement such as verbal praise, reward points, and special privileges whenever students arrived on time. Data were analyzed descriptively using frequency counts of tardiness per week and visualized through graphs to identify behavioral trends. The results revealed a significant decrease in tardiness frequency from the baseline to the intervention phase, with stability maintained during the second baseline. These findings confirm that DRL is a simple, effective, and contextually relevant strategy for fostering student punctuality and discipline. The novelty of this study lies in applying differential reinforcement in a public junior high school setting with limited resources, contributing fresh insights into the Indonesian context of classroom management.